2021
DOI: 10.2106/jbjs.20.01640
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Algorithms Predict Functional Improvement After Hip Arthroscopy for Femoroacetabular Impingement Syndrome in Athletes

Abstract: Background: Despite previous reports of improvements for athletes following hip arthroscopy for femoroacetabular impingement syndrome (FAIS), many do not achieve clinically relevant outcomes. The purpose of this study was to develop machine learning algorithms capable of providing patient-specific predictions of which athletes will derive clinically relevant improvement in sports-specific function after undergoing hip arthroscopy for FAIS.Methods: A registry was queried for patients who had participated in a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…Although there remains a paucity of literature studying the achievement rates and predictors of clinically significant outcomes for the IHOT-12 score, previous studies have reported that presence of anxiety/depression, 7,15,23 back pain, 24,46 chronic symptom duration, 20,21 and higher preoperative outcome scores negatively influence other clinically significant outcomes after hip arthroscopy. 9,22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there remains a paucity of literature studying the achievement rates and predictors of clinically significant outcomes for the IHOT-12 score, previous studies have reported that presence of anxiety/depression, 7,15,23 back pain, 24,46 chronic symptom duration, 20,21 and higher preoperative outcome scores negatively influence other clinically significant outcomes after hip arthroscopy. 9,22…”
Section: Discussionmentioning
confidence: 99%
“…Ramkumar et al 37,38 have demonstrated that ML is an appropriate and accurate method for clinically meaningful outcome prediction after osteochondral allograft in the knee using data sets as small as 153 patients. Kunze et al 22 reported that ML provided reliable and accurate predictions in determining whether athletes who underwent hip arthroscopy would experience clinically meaningful improvements in sports-specific function. However, little remains known about the association between demographics, preoperative PROMs, clinical examination data, and routine imaging in predicting clinically meaningful outcomes for more contemporary outcome measures such as the IHOT 12-Item Questionnaire (IHOT-12).…”
mentioning
confidence: 99%
“…Several recent studies have also demonstrated the applicability of machine learning in prognostication of functional outcomes after hip arthroscopy using outcome scores such as the mHHS, Hip Outcome Score-Activities of Daily Living Subscale, and Hip Outcome Score-Sport Specific Subscale. [9][10][11]18 This study relied on the TRIPOD statement as a tool to provide high-quality evidence and improve the quality of reporting. 5 The TRIPOD statement includes recommendations for reporting that improve the transparency of the methodology and help with the generalization of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have also demonstrated the applicability of machine learning in prognostication of functional outcomes after hip arthroscopy using outcome scores such as the mHHS, Hip Outcome Score–Activities of Daily Living Subscale, and Hip Outcome Score–Sport Specific Subscale. 9 -11,18…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, machine learning has demonstrated validity in predicting clinically meaningful outcome improvement after common orthopaedic procedures. 15 17 , 23 This allows for risk prediction at the individual patient level, overcoming the limitations of current sports medicine literature. The purpose of the current study was to develop machine learning algorithms to predict achievement of the MCID on the IKDC score at a minimum 2-year follow-up after ACLR.…”
mentioning
confidence: 99%